Vaccination strategies in the disease–behavior evolution model - Zhou, Lu; Dai, Jinying; Qu, Bo; Li, Cong (Frontiers in Physics, 2024)
Previous studies on the co-evolving between vaccination strategies and epidemics mainly assumed that the vaccination strategies are made in the period between two spreading seasons. However, individual cognition during the spreading seasons might also alter the vaccination strategy and inversely influence the epidemic spreading. We propose a coupled disease-behavior model to describe the dynamic evolution of vaccination behavior during the spread of infectious diseases. The model integrates a susceptible-infected-vaccinated (SIV) model with the diffusion of vaccination behavior. We focus on the trade-off between perceptions of infection risk and vaccination behaviors of neighbors, characterizing individual vaccination opinions. We introduce an opinion critical value to map vaccination opinions into the vaccination behavior. The vaccination coverage of the disease-behavior model is studied in network models and real-world networks. In addition, when societal costs are measured based on the degree of initial vaccinees, the cost of randomly selecting initial vaccinees is lower than selecting individuals with high or low degrees as vaccinees. Evaluating an individual's ability to transmit vaccination behavior based on the neighbor number is inappropriate. We find that the impact of effective spreading rates on group vaccination is not one-sided and that reducing fear and highlighting the dangers of infectious diseases are crucial to increasing vaccination coverage.